2020
DOI: 10.24329/aspikom.v5i1.533
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneration Comparison of the Spread Pattern of Hoax

Abstract: Social media is one of the fields for spreading hoaxes or fake news. This study compared the spread patterns of hoax between Generation X and Generation Z. This study used McPrenski's Generation Theory and the concepts of DeFleur and Ball-Rokeach regarding social categories theory. A survey was conducted in Sleman Regency, Yogyakarta province, and the sample size was 240. The research was held before the Indonesia General Election2019 due to the high spread of political hoaxes. The hypothesis was tested using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The concept of receiving information in each age group is another obstacle, considering that each generation has a different social perspective in responding to a piece of information (Susilo et al, 2020). It is also closely related to the level of digital literacy that is relatively low and is one form of the digital divide experienced by society (Hasfi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of receiving information in each age group is another obstacle, considering that each generation has a different social perspective in responding to a piece of information (Susilo et al, 2020). It is also closely related to the level of digital literacy that is relatively low and is one form of the digital divide experienced by society (Hasfi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to note that adult women's abilities to improve their digital skills are lower than younger women (Long et al, 2023;Sitepu & Rajagukguk, 2022). Each generation creates a social perspective in responding to new information (Susilo et al, 2020), and studies confirmed that Generation Z is more familiar with technology and motivated to acquire new knowledge about digital innovation than the older generations (Sitepu & Rajagukguk, 2022).…”
Section: Core Issues On Women's Digital Competence In Indonesiamentioning
confidence: 99%
“…Jumlah situs di Indonesia yang diblokir Kementerian Komunikasi dan Informatika sampai dengan akhir 2019, karena mengandung konten negatif mencapai 1.857.907 situs. Data ini masih belum ditambah dengan ratusan ribu akun media sosial yang terindikasi menyebarkan hoaks dan informasi palsu (Susilo et al, 2020). Hoaks adalah informasi atau berita yang berisi hal-hal yang belum pasti atau yang benar-benar bukan fakta (Juditha, 2018).…”
Section: A Latar Belakangunclassified